Influence of gamma radiation of indoor radon decay products on absorbed dose rate - Pilkyte, Laima; Butkus, Donatas (Journal of Environmental Engineering and Landscape Management, 2005)
A survey of absorbed dose rate and indoor radon concentration in multistorey houses was carried out. The main source of radon in such houses is construction materials. There is a relationship between absorbed dose rate and indoor radon concentration. This relationship is rather complicated and different for different premises. It depends on the geometry of premises and other characteristics which influence the distribution of indoor radon daughters. Increment of absorbed dose rate per unit of increment of indoor radon concentration depends on the concentration of indoor radon, floor where premises are situated, geometry of premises. The results of this study might help to assess the dose due to indoor radon which originates from construction materials. Radono skilimo produktų gama spinduliuotės įtaka sugertosios dozės galiai patalpose Santrauka. Buvo atlikti sugertosios dozės galios ir radono tūrinių aktyvumų matavimai daugiaaukščiuose namuose. Pagrindinis radono šaltinis tokiuose pastatuose yra statybinės medžiagos. Nustatyta, kad sugertosios dozės galia ore priklauso nuo radono tūrinio aktyvumo patalpose. Šis ryšys susijęs su patalpų geometrija ir kitais parametrais, kurie turi įtakos radono skilimo produktų pasiskirstymui patalpose. Sugertosios dozės galios pokytis priklauso nuo radono tūrinio aktyvumo, aukšto, kuriame yra patalpos, patalpų geometrijos. Šio darbo rezultatus galima panaudoti iš statybinių medžiagų išsiskyrusio radono spinduliuotes lemiamai dozei įvertinti. Reikšminiai žodžiai: gamtiniai radionuklidai, išorinė apšvita, radonas patalpose, sugertosios dozės galia, statybinės medžiagos. First Published Online: 14 Oct 2010